PENERAPAN ALGORITMA GENETIKA (GA) PADA PENJADWALAN PENGAMANAN LINGKUNGAN - Religian Restu Priharnanto (2021)
This research was conducted to facilitate the creation of environmental safety schedules in RT 6. Genetic Algorithm is a discovery algorithm based on the mechanism of biological evolution. Diversity in biological evolution is the variation according to chromosomes between individual organisms. This chromosomal variation will affect the rate of production and the level of the organism's ability to live. The author builds an environmental security scheduling application using genetic algorithms as an alternative to replace environmental security scheduling which was previously manually converted into an application to make it easier and faster. For the initial stage of the research, the authors seek information about the manual scheduling system. The second stage the author makes a scheduling application using the application to make it more effective and fast and minimize the occurrence of conflicts. In the third stage, the writer collects citizen data to make a schedule for environmental protection. To produce optimal scheduling the author uses a genetic algorithm. The fourth stage provides scheduling results from data that has been collected and selected randomly with an optimal fitness value. The results of this study are a web-based application that makes it easy for users so that when making a security schedule they do not use the manual method because it takes 2 hours, while using the application only takes 2 minutes.